Kelebihan dan Kelemahan dalam Penggunaan Object Oriented Programming - Eva Darwisah Harahap; Zulaiha Siregar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In general, many programming languages have been provided for making applications, both of small and large value, which are useful for answering various other user needs. Object-oriented programming is an object-oriented programming paradigm, all data and functions contained in it are wrapped in classes or object objects. , compared to structured programming logic where each object can receive messages, process data, and also send messages to other objects, object-oriented programs were discovered in the 1960s there starting from a structured program creation and then this method was developed from C and Pascal.